Study of Serum Calcium and Potassium Level in Newly Detected Hypertensives and its Correlation with the Severity of the Disease - Fakruddin, Dr Mohammad; Abbas, Dr Mohammad; Tabassum, Dr Shainaz; Begum, Dr Farzana (International Journal of Innovative Research in Medical Science, 2025)
Background and Objectives: Serum Calcium and serum potassium are two important elements in regulating cardiovascular functions. Alteration in these have been shown to be associated with hypertension. Serum calcium levels are found to be significantly reduced in hypertension, however serum potassium levels have been found to be variable in hypertensive patients. Methods: This study was conducted in tertiary care hospital which is a case control study in which newly detected patients with essential hypertension are enrolled. Serum calcium and serum potassium were estimated in all the patients at the time of study. Serum potassium levels were correlated with age, gender, grades of hypertension and ECG changes. Results: A total of 75 patients were studied, 50 were cases and 25 controls. majority were in the age group of 46 to 55 years , mean ages among the cases and controls were 49.52±4.67 years and 51.80±9.61 years respectively .Mean systolic (SBP) among the cases and controls were 165.40±10.93 mm Hg and 127.92±10.01 mm Hg and the mean diastolic blood pressures (DBP) were 96.80±7.13 mm Hg and 77.04±5.29 mm Hg respectively .serum calcium levels were significantly lesser among the cases of hypertension (8.05±0.41 mg/dL) compared to controls (8.68±0.34 mg/dL) who did not have hypertension (P<0.05). Serum potassium levels did not vary among the cases (4.51±0.42 mmol/L) and controls (4.64±0.48 mmol/L) (P>0.05). Corrected serum calcium levels were decreased in patients with newly detected hypertension compared with controls. However serum potassium level did not show any difference between cases and controls. Significant negative correlation was found between corrected serum calcium levels and systolic and diastolic blood pressure. Conclusion: Corrected serum calcium levels were reduced in patients with essential hypertension and significant negative correlation was seen between corrected serum calcium levels and systolic and diastolic blood pressures but no correlation was found with serum potassium levels.